[(x**-2) y**2 .z)**2]**2 (x**-8)(y**8)(z**4)
----------------------- = -----------------------------
[x**2 . y**3]**2 (x**4) (y**6)
(y**8)(z**4) (y**2)*(z**4)
--------------------- = -------------
(x**12) (y**6) (x**12)
30.78cm 32.36cm 73.14cm the process is shown in the following picture
Answer:
x = 4, y = -4
Step-by-step explanation:
9x + 3y = 24
3x + y = 8 divide both sides by 3
y = 8 - 3x subtract 3x from both sides
2y + 4x = 8
2(8 - 3x) + 4x = 8 replace y with 8 - 3x
16 - 6x + 4x = 8 distributive property
-6x + 4x = 8 - 16 subtract 16 from both sides
-2x = -8 divide both sides by -2
x = 4
y = 8 - 3x
y = 8 - 3(4) replace x with 4
y = 8 - 12
y = -4